Introducing PT. Adikarya Multi Teknologi Mandiri Using a Company Profile - Sheryl Keren Muliadie (Institute of Research and Community Outreach - Petra Christian University, 2020)
PT. Adikarya Multi Teknologi Mandiri is a business-to-business company involved in vacuum coating industry. Its folder-shaped company profile specifically targets purchasing personnels and is tailor made to suit procurement process during an open tender; acting as the extension of a name card. Hence, the company profile pays special attention to design that enables easy reading which showcases the company’s products and services. Texts are kept short and fully focused on highlighting the company’s unique selling preposition to entice offers. The design is based on Gestalt’s Principle and Contemporary Color Theory by Steven Bleicher, while the text follows Sally Hogshead’s Fascinate: How to Make Your Brand Impossible to Resist and Blythe’s Essential of Marketing. Keyword: Business to business, Company Profile, Short Company Profile